„I really love that guy!“: Romantische Liebe als Weg zur Moderne im regionalen Kontext Singapurs und Malaysias - Thimm, Viola (Asien, 2016)
This ethnographic article analyzes how a female social actor negotiates the concept of "romantic love" in the regional contexts of Singapore and Malaysia, in order to develop herself out of her native social environment. Based on her ethnic-, religious-, and education-based belonging, she characterizes this environment as "traditional". In this respect, romantic love is a means by which to identify herself as "modern". Malaysia is a multicultural society with 65 percent Malay Malaysians and so-called "indigenous people", 26 percent Chinese Malaysians, and 7 percent Indian Malaysians. Singapore is meanwhile, as a "modern Southeast Asian metropolis" that is comprised of the same ethnic groups due to its historic ties with Malaysia, Chinese dominated however. In both states the concept of romantic love developed in the 1960s among all three of the aforementioned ethnic groups as an alternative to arranged marriage. The process to identify oneself as a modern woman through practices of romantic love is mostly negotiated by Christian Chinese Malaysian women who have earned a high degree of formal education. They intensify this process through taking a migration step to "modern" Singapore. In the local context the concept of romantic love is defined through having a partner before marriage, being sexual active with him, and then strengthening this relationship through a "white wedding". Romantic love in Singapore and Malaysia is based on practices of adaption of the concept as developed in the modern era of the Western world, which developed on the basis of that region's subjectivity, individuality, and the differentiation between public and private spaces. (Asien/GIGA)